Fibrinolytic Dysregulation in Total Joint Arthroplasty Patients: Potential Clinical Implications. (May 2016) - Guler, Nil; Burleson, Andrew; Syed, Daneyal; Banos, Andrew; Hopkinson, William; Hoppensteadt, Debra; Rees, Harold; Fareed, Jawed
Background: The alterations of the fibrinolytic components in osteoarthritic joint disease and their postsurgical modulation are not clearly understood. Preexisting hemostatic dysfunction may lead to both thrombotic and bleeding events in these patients. Aim: To profile fibrinolytic parameters in patients undergoing total joint arthroplasty prior to and on postoperative day 1. Methods: A total of 98 total joint arthroplasty patients were included in this study. Blood samples were drawn preoperatively and on postoperative day 1 status posttotal knee or total hip arthroplasty surgery.d -Dimer, plasminogen activator inhibitor 1 (PAI-1), and tissue plasminogen activator (tPA) were measured using commercially available enzyme-linked immunosorbent assay kits. Antiplasmin activity was measured by using a functional method. Results: Preoperative PAI-1, d -dimer, and tPA levels were significantly higher in arthroplasty patients compared to healthy controls. Preoperative antiplasmin level was lower than controls. Postoperative levels of PAI-1 andd -dimer were increased compared to preoperative values. Postoperative antiplasmin values were lower than preoperative levels. Changes in tPA was not significant. There was no correlation between preoperative PAI-1 andd -dimer levels. Pre- and postoperative percentage changes in each individual were calculated for PAI-1, d -dimer, tPA, and antiplasmin. There was a positive correlation betweend -dimer and PAI-1. Negative correlations between antiplasmin andd -dimer and between antiplasmin and PAI-1 were noted. Conclusion: These results confirm the perturbation in the fibrinolytic system of patients undergoing total joint arthroplasty surgery. Surgical intervention may also enhance the observed changes. The alterations in the fibrinolytic system may lead to the observed hemostatic complications such as bleeding, hematoma formation, or potential need for blood transfusion.